DESIGN AND ANALYSIS OF AN AERODYNAMIC DOWNFORCE PACKAGE FOR A FORMULA STUDENT RACE CAR - Abid, Muhammad; Wajid, Hafiz Abdul; Iqbal, Muhammad Zohair; Najam, Shayan; Arshad, Ali; Ahmad, Ammad (IIUM Engineering Journal, 2017)
This paper presents design of aerodynamic downforce generating devices (front wing, rear wing and diffuser) to enhance the performance of the Formula Student Race Car using numerical and experimental studies. Numerical results using computational fluid dynamics (CFD) studies were primarily validated with the experimental results performed in the wind tunnel. It was concluded that the use of a downforce package can enhance the performance of the vehicle in the competition.